PERBEDAAN SIKAP POSITIF SISWA SMA ANTARA YANG DIBERI PENDEKATAN PBM BERBANTUAN CABRI 3D DENGAN PEMBELAJARAN LANGSUNG - Elfrida Sidabutar (Universitas Quality, 2018)
The aim of this study was to analyze whether difference inrcease: Positive Attitude of students who are recieved PBL approach assisted Cabri 3D better than who are recieved direct instruction. Type of this study is semi experimental research with pretest-posttest control group design. The sample was class X of SMA Santu Petrus Sidikalang then randomly selected two classes. Data was analyzed using analyze of covariance (Anacova). The main result of this study are difference inrcease: Of Positive Attitude of students who are recieved PBL approach assisted Cabri 3D better than who are recieved direct instruction. Researchers suggest: Problem basedlearning approach assisted Cabri 3D can be used as an alternative for implementing innovative math learning to increasing positive attitude of students toward mathematics.